Staying connected: the importance of timely communication for young people living with a long-term condition and their clinical teams. Issue 13 (3rd October 2022) - Bryce, Carol; Ignatowicz, Agnieszka; Huxley, Caroline; Hamilton, Kathryn; Dliwayo, Thandiwe; Forjaz, Vera; Sturt, Jackie; Griffiths, Frances
ABSTRACT: Timely communications are important in enabling young people with long-term conditions to stay engaged with their health and manage their condition successfully. This study considers the role of digital communication in helping young people engage with services and the clinical teams providing their care. Data are drawn from 165 young people and 173 NHS staff across 20 clinical settings in the UK treating a variety of long-term conditions. Although not the focus of the main study the intersection of digital technologies and timely communication in keeping young people engaged was apparent. We drew on theories of time to understand how time was conceptualised and used in the digital communications between young people and their clinical teams. Through the lens of time we show that digital communications are valued differently by young people with long-term conditions and their clinical teams. In the current policy landscape where there is an emphasis on digital technology understanding the temporalities of different groups will help in the introduction of appropriate digital communications channels. Done well digital communications have the potential to improve young patients' autonomy but this must be balanced with the needs of clinical teams, particularly loss of control over work patterns.